Advancing Health Equity through Organizational Mentoring Policies at Minority-Serving Institutions - Johnson Hemming, Japera (Ethn Dis, 2019)
OBJECTIVE: Morehouse School of Medicine, a collaborative partner in the National Research Mentoring Network, established the Mentoring Academy Institutional Planning Forum (MA Forum) to help minority-serving institutions (MSI) optimize research mentoring. In this commentary, we describe the policy workshop and review survey data from six MSIs to assess the current state of organizational policies and activities that advance research mentoring. PARTICIPANTS: Twenty-eight institutional leaders, representing six MSIs, participated in an MA Forum between May 20, 2016 and May 11, 2017. METHODS: After describing the MA Forum’s background, design and recruitment strategy, we present a synthesis of institutional summaries built from responses to a 45-item survey that explored existing mentoring infrastructure, policies, and activities at each institution. RESULTS: There is a heavy reliance on extramural funds to facilitate research mentoring initiatives. Mentoring policies and activities were most often governed by individual programs rather than the institution. Thus, the research mentoring expertise was concentrated at the local level, which may prevent opportunities for future scalability and optimization. CONCLUSIONS: Given these findings, we offer recommendations to help MSIs establish a mentoring culture backed by institutional policy.